Shark spade: arm chair / Amirul Hafiz Samsuri - Samsuri, Amirul Hafiz (College of Creative Arts, Universiti Teknologi MARA Kedah Branch, 2022)
This Armchair is based on a shark. Sharks are a group of elasmobranch fish characterized by a cartilage skeleton, five to seven-gill slits on the side of the head, and pectoral fins not attached to the head. Modern sharks have been classified in the Selachimorpha (or Selachii) clade and are the sister group to the rays. Shark Spade is a seat taken from part of the shark's body, namely the dorsal fins. the chair is made of wood and metal. Whole wood uses the mortise method while metal uses the welding method. This Shark Spade is perfect to place in the living room. Shark Spade, using oak wood and gray (metal) colors. The Shark Spade has safe and user-friendly ergonomics. Humans observed and tried to learn about natural forms and structures. Designers have also observed how life proceeded in nature and began to develop the furniture by observing or imitating the natural structures. Nature gave them plenty of opportunities with its admirable mechanisms, designs, and potential to enrich various aspects of life. As a result of the increase of our accumulation of knowledge and the development of technological opportunities, this potential reveals itself a bit more every single day to become furniture designers, students need to clearly define the problems and propose the possible solution related to furniture design. In this lesson, students are encouraged to explore and developed furniture that can fit their ever-changing needs. Apart from that, they can create new furniture designs that can give awareness of nature and inspire others.